Strategies for the integration and development of standards for the Global Information Infrastructure. - RYAN, Henry J.F. (1996)
Presents the highlights and recommendations identified by the GII Seminar. Identifies three specific groups, viz., (1) Criteria for successful GII standardization; (2) Provision of transparent user-oriented information; and (3) Re-engineering - to improve standards development and use. Also lists other issues that would require specific action.